ARTI AYAH BAGI ANAK PASCA KONVERSI AGAMA Sebuah Studi Fenomenologis dengan Pendekatan Interpretative Phenomenological Analysis (IPA - Pamungkas, Gagah Putra; Abidin, Zaenal (Empati, 2017)
This study aims at understanding the experiences of children who have fathers with different religion, especially on sons. The researcher found three subjects that fit into the criteria through key person. The subjects of the study were three people and are all male. The characteristics of the research include having a biological father with different religion for a minimum three years and are between 20 to 25 years old. This study used Interpretative Phenomenological Analysis (IPA) method to analyze the data gathered through interview. All the subjects have different religion from the fathers due to religion conversion. The result of this study shows the magnitude of father’s influence on son with different religion. The father’s figure as a role model has a significant influence on all of subjects’ development, although it cannot be denied that the feeling of sadness appeared in all subjects for not being able to do religious worship with the father. This study found a uniqueness in the second subject, that is problematic with the father. The problematic with the father causes the second subject feels the lack of father’s presence and confused about the father figure, so that the second subject could look down and be indifferent to the father.